Pengaruh biaya produksi terhadap penetapan harga jual kue kering - bakpia pada UD. New Tweety Desa Takeran RT 04 RW 01 Kecamatan Takeran Kabupaten Magetan - Heniy Undaryani Dewi (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study aims to determine Production Costs incurred by the company UD. New Tweety-Magetan, and to determine the effect on the production cost selling price determination pastries bakpia-Bakpia At UD. New Tweety. The sampling technique in this study using purposive sampling technique that uses the samples for 4 of the last period started the company UD. New Tweety-Magetan founded. Data collection method used is observation, interview and documentation methods. Analysis of the data used to use Descriptive Statistics analysis using Simple Linear Regression Analysis, The results showed that the positive influence between the production cost of the determination of the selling price. This is shown by a simple linear regression equation Y = 91.880 + 0.708 X that could mean that in any rise in the cost of production is always followed by a rise in selling prices, as well as vice versa in any reduction in production costs always follow gathering decrease in selling prices. In this study the effect of production cost and the selling price by 65.7% and34.3% influenced by conditions or other variables such as market demand and consumer tastes will be Pastries Bakpia.